Formação na Modalidade a Distância pela Universidade Aberta do SUS: Estudo Qualitativo sobre o Impacto do Curso na Prática Profissional - Marin, Maria José Sanches; Nascimento, Edinalva Neves; Tonhom, Silvia Franco Da Rocha; Alves, Suelen Beatriz Alonso Deponti; Girotto, Marcos Antonio; Otani, Marcia Aparecida Padovan; Silva, Luís Carlos De Paula E (Associação Brasileira de Educação Médica, 2017)
ABSTRACTIntroductionThe proposals of the current National Health Policy imposes the need for transformation in the forms of health care, consequently, in team work behaviors to achieve a larger view on the health-disease process. Therefore, there is a need to train health professionals in the technical, ethical and political aspects to the transformation of work processes. Then it’s has been proposed by the Ministry of health for courses in distance mode.ObjectiveTo understand the impact of The Specialization Course in Family Health Care developed in the distance mode (DE) in professional practice of graduates.Methodqualitative study accomplished through 24 interviews with graduates (11 dentists, 08 nurses, 05 doctors) from a Specialization Course in Family Health Care developed in DE mode conducted by Open University of Brazilian Unique Health System UNA-SUS in collaboration with the Federal University of São Paulo (Unifesp). The analysis was directed by assumptions of hermeneutical thinking-dialectic, which is included in interpretative perspective of qualitative methodologies.ResultFor the graduates, it was possible to incorporate a broader view of the health needs of the population and the bond establishment, what is essential to the process and innovative care; recognition of the role and the importance of the different team members, leading to new ways to make care and a different vision about the meaning of the family health strategy; to improve the managing process through shared decisions, to organize the work process and to considerate the epidemiological data for the action planning, what involves managements of people, process and information.ConclusionPermanent Education Movements like this are essential for the effective implementation of the elements and guideline of SUS, this brings the necessary concepts and practices to a new way of acting and thinking about health.

RESUMOIntroduçãoAs propostas da atual Política Nacional de Saúde impõem a necessidade de transformação nas formas de cuidado em saúde e, consequentemente, nas relações de trabalho da equipe para se obter uma visão ampliada sobre o processo saúde-doença. Existe, portanto, necessidade de instrumentalizar os profissionais da saúde nos aspectos técnicos, éticos e políticos para a transformação de seus processos de trabalho, sendo que para isso, vem sendo proposto pelo Ministério da Saúde cursos na modalidade a distância.ObjetivoCompreender o impacto do Curso de Especialização em Saúde da Família desenvolvido na modalidade a distância na prática profissional de egressos.MétodoEstudo qualitativo realizado por meio de 24 entrevistas com egressos (11dentistas, oito enfermeiros e cinco médicos) de um curso de especialização em Saúde da Família na modalidade a distância realizado pela Universidade Aberta do Sistema Único de Saúde UNA-SUS em parceria com a Universidade Federal de São Paulo (Unifesp). A análise teve como direção os pressupostos do pensamento hermenêutico-dialético, que se insere na perspectiva interpretativa das metodologias qualitativas.ResultadoPara os egressos, foi possível incorporar uma visão ampliada das necessidades de saúde da população e do estabelecimento de vínculo, o que é essencial ao processo de cuidado ampliado e inovador; reconhecer o papel e a importância dos diferentes profissionais da equipe, levando a novas formas de fazer o cuidado e a uma visão diferenciada sobre o sentido da Estratégia Saúde da Família; melhorar o processo de gestão por meio de decisões compartilhadas, organizar o processo de trabalho e considerar os dados epidemiológicos no planejamento das ações, o que envolve a gestão de pessoas, dos processos de trabalho e da informação.ConclusõeMovimentos de Educação Permanente como este são essenciais à implantação efetiva dos princípios e diretrizes do SUS, uma vez que aproxima os profissionais de conceitos e práticas necessárias a um novo modo de agir e pensar em saúde.
Education in Distance Mode Conducted by Open University of Brazilian Unique Health System (SUS): Qualitative Study about the Impact of the Course on Professional Practice
Keywords: Teaching; Distance Education; Family Health Care; Staff Development; Ensino; Educação a Distância; Saúde da Família; Desenvolvimento de Pessoal